Respuesta :
The first step to solve this equation is to move the variable to the left side of the equation and change its sign
4z + 3z + 5 = -8
Move the constant to the right side of the equation and change its sign
4z + 3z = -8 - 5
Collect the like terms on the left side of the equation
7z = -8 - 5
Calculate the difference
7z = -13
Lastly,, divide both sides of the equation by 7 to find out what z is
z = -[tex] \frac{13}{7} [/tex]
This means that z in your equation is -[tex] \frac{13}{7} [/tex],, or 1[tex] \frac{6}{7} [/tex] when simplified.
Let me know if you have any further questions
:)
4z + 3z + 5 = -8
Move the constant to the right side of the equation and change its sign
4z + 3z = -8 - 5
Collect the like terms on the left side of the equation
7z = -8 - 5
Calculate the difference
7z = -13
Lastly,, divide both sides of the equation by 7 to find out what z is
z = -[tex] \frac{13}{7} [/tex]
This means that z in your equation is -[tex] \frac{13}{7} [/tex],, or 1[tex] \frac{6}{7} [/tex] when simplified.
Let me know if you have any further questions
:)
Answer:
13/7
Step-by-step explanation:
3z + 5 = 4z - 8
3z - 4z = -5 - 8
-1z = -13
-1/-1 (fraction) = -13/-1
z = 14